Analisis Capital Asset Pricing Model (CAPM) Sebagai Dasar Pengambilan Keputusan Berinvestasi Saham (Studi pada Indeks Bisnis-27 di Bursa Efek Indonesia) - Hasan, Nurain; Pelleng, Frendy A. O.; Mangindaan, Joanne V. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study were: (1) To help investors pick efficient and inefficient stocks, (2) Investors know which stocks that have an optimal return and appropriate risk, (3) Investors know about CAPM metodh in determining the best investment decisions. CAPM is a model for estimating returns earned on risky securities or as a benchmark in evaluating the rate of return on an investment. The samples were selected by purposive sampling technique, the samples were determined by the specific criteria: (1) Companies listed on the Indonesia Stock Exchange belonging to the Business-27 stock index (2) Companies whose shares are included in the Business-27 stock index consistenly. The selection criteria in this study is choosing the efficient stocks in which individual return > expected return (Ri>ERi). Efficient collection of shares must be a priority in investment decisions made only efficient stocks that can be purchased. The results of this study indicate that: There are 18 stocks included on Efficient shares ie AKRA, BBCA, BBNI, BBRI, BMRI, CPIN, GGRM, INDF, INTP, PGAS, SMGR. These shares have a Ri> ERi value, investment decisions should be taken by investors was to buy efficient stocks. Based on data analysis there is a non-linear relationship between systematic risk and expected stock returns.